Compatibilidad floral en cerezos y guindos - Welkerling, Emma M. L. (1961)
Two years trials made in order to determine the possible floral self-compatibility in a plantation of 65 varieties of cherries, sour cherries and interspecific hybrids. The results agree with those obtained abroad because the cherries and also the hybrids proved to be completely sel-incompatibles; only one variety of sour cherry: Wye Morello was self-compatible.